2017
DOI: 10.1002/adma.201705017
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure‐Induced Comminution and Recrystallization of CH3NH3PbBr3 Nanocrystals as Large Thin Nanoplates

Abstract: High pressure (HP) can drive the direct sintering of nanoparticle assemblies for Ag/Au, CdSe/PbS nanocrystals (NCs). Instead of direct sintering for the conventional nanocrystals, this study experimentally observes for the first time high-pressure-induced comminution and recrystallization of organic-inorganic hybrid perovskite nanocrystals into highly luminescent nanoplates with a shorter carrier lifetime. Such novel pressure response is attributed to the unique structural nature of hybrid perovskites under hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 48 publications
6
110
0
Order By: Relevance
“…Pressure, as a clean tuning “knob”, can effectively modulate the distortion degree and crystal structures of LDHPs without changing the chemical composition. [ 9–17 ] The efficient bandgap tuning and emission enhancement in LDHPs render the pressure a robust tool to achieve the optimization of optical properties. [ 18–20 ] However, deep insight into relationship between the distorted formation of octahedral frameworks and controllable emission enhancements of LDHPs still remained obscure as yet.…”
Section: Figurementioning
confidence: 99%
“…Pressure, as a clean tuning “knob”, can effectively modulate the distortion degree and crystal structures of LDHPs without changing the chemical composition. [ 9–17 ] The efficient bandgap tuning and emission enhancement in LDHPs render the pressure a robust tool to achieve the optimization of optical properties. [ 18–20 ] However, deep insight into relationship between the distorted formation of octahedral frameworks and controllable emission enhancements of LDHPs still remained obscure as yet.…”
Section: Figurementioning
confidence: 99%
“…As a powerful and clean tool, hydrostatic pressure can effectively tune the crystal strucutre and electronic landscapes of 2D perovskite materials without chemical interference; it uniquely accessed novel photophysical and transport properties not accessible by traditional ways, providing a perfect way to confirm our conjecture . In recent years, high pressure research of halide perovskites mainly focused on 3D structure, realizing the fine tuning of optical and electronic properties by lattice compression . Unprecedented simultaneous band‐gap narrowing and carrier lifetime prolongation of FAPbI 3 were achieved by modifying the bond length and bond angle under mild pressure .…”
mentioning
confidence: 94%
“…[5] Pressure is ac lean tuning knob for modulating crystal structures and electronic configurations without changing the chemical composition. [6] In recent years,3 Dh alide perovskites have been studied extensively upon compression, and av ariety of novel phenomena have been observed including pressure-induced phase transformations, [7] amorphization, [8] metallization, [9] band gap modulation, [10] and increased electronic conductivity. [11] However,o nly af ew studies on 2D halide perovskites with compression have been reported thus far.…”
mentioning
confidence: 99%